Capturing patient experience: does quality-of-life appraisal entail a new class of measurement?. - Schwartz, Carolyn E.; Stark, Roland B.; Rapkin, Bruce D. (Tufts University. Tisch Library., 2020)
Keywords: Appraisal, Measurement theory, Clinimetric, Psychometric, Idiometric, Causal indicator, Effect indicator, Formative versus reflective measurement model, Response shift.; Springer Open.